2003
DOI: 10.1093/bja/aeg207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intraoperative blood transfusion practice during elective non-cardiac surgery in an Indian tertiary care hospital

Abstract: Current intraoperative blood use is sub-optimal. Intraoperative haemoglobin estimation is an effective and simple measurement to improve appropriate use of blood. The indication for transfusion should be recorded in the case notes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
3
17
1
Order By: Relevance
“…20 It was found that criteria for appropriate transfusion were fulfilled by 54% in the public and 69% in the private hospital. This finding was, however, lower compared to previous studies conducted in other hospitals in Pakistan where appropriate transfusions were 80-85% but in those studies no standard guidelines had been used or at least not mentioned in the methodology.Even in developed countries 21 inappropriate transfusion is in the range of 18-35%, while in India the range varied from 30% to 60% 22,23 which is almost the same as in this study.…”
Section: Resultssupporting
confidence: 82%
“…20 It was found that criteria for appropriate transfusion were fulfilled by 54% in the public and 69% in the private hospital. This finding was, however, lower compared to previous studies conducted in other hospitals in Pakistan where appropriate transfusions were 80-85% but in those studies no standard guidelines had been used or at least not mentioned in the methodology.Even in developed countries 21 inappropriate transfusion is in the range of 18-35%, while in India the range varied from 30% to 60% 22,23 which is almost the same as in this study.…”
Section: Resultssupporting
confidence: 82%
“…This is in agreement to Niraj G et al 6 Hemoglobin Hb was <8 (males-2.5%, females-1.5%), 8-10 (males-6%, females-4%), >10 (males-42%, females-44%). This is in accordance to Mallet et al…”
supporting
confidence: 92%
“…Similar studies describing blood use have been conducted in developing countries but are generally limited in sub-Saharan Africa [19][20][21][22]. The few available studies from the region are restricted to specific wards or regional or tertiary hospitals, and only cover short periods [23,24].…”
mentioning
confidence: 99%